Retroperitoneal fibrosis: A rare cause of both ureteral and small bowel obstruction - Aziz, Faisal (Baishideng Publishing Group Co., Limited, 2006)
Retroperitoneal fibrosis (RPF) is a rare condition of unclear etiology. It can cause ureteral obstruction. We present the unique case of a 54 years old female, who initially presented with spontaneous perforation of the cecum. Upon exploring the abdomen, the classical glistening white, unyielding retroperitoneal fibrosis was encountered. A right hemicolectomy was performed. Subsequently, the patient presented with bilateral ureteral obstruction, and later on with small bowel obstruction. Ureteral obstruction was treated with stents, and small bowel obstruction was treated with bypass. To our knowledge no case of idiopathic RPF presenting with features of both bilateral ureteral and small bowel obstruction has been reported in the literature.